Pressure-sensitive halogen-free high-stripping-resistance resin glue solution, copper-clad plate and preparation method of pressure-sensitive halogen-free high-stripping-resistance resin glue solution

By using pressure-sensitive halogen-free and high peel-resistant resin glue to quickly self-crosslink at lower temperatures, the problems of energy waste in high temperature and high pressure in traditional copper clad plate production and high internal stress in products are solved, and high efficiency is achieved. Low-cost copper clad plate preparation, with performance comparable to FR-4.

CN119505460AInactive Publication Date: 2025-02-25SHANDONG JINBAO ELECTRONICS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411517882.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The production of traditional copper clad plate requires long-term pressure suppression at high temperature and high pressure, resulting in waste of energy and large internal stress of the product, affecting processing performance.

Method used

The copper clad plate is prepared by a pressure-sensitive halogen-free and highly peel-resistant resin glue solution, including phenyl silicone resin, acrylic resin, modified epoxy resin, etc., by rapid self-crosslinking at lower temperatures.

Benefits of technology

Fast self-crosslinking at lower temperatures, saving energy, reducing product warping and flow of glue, the copper clad plate produced has a performance comparable to that of ordinary FR-4 copper clad plates and is highly resistant to peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107214250000021
    Figure BDA0005107214250000021
  • Figure BDA0005107214250000081
    Figure BDA0005107214250000081
Patent Text Reader

Abstract

The invention belongs to the technical field of production of copper-clad plates, and relates to a pressure-sensitive halogen-free high-stripping-resistance resin glue solution, a copper-clad plate and a preparation method of the resin glue solution, and the resin glue solution comprises the following components in parts by weight: 5-15 parts of phenyl silicone resin; 10 to 25 parts of acrylic resin; 5-20 parts of modified epoxy resin; 10 to 20 parts of a diene copolymer; 18 to 25 parts of acrylic acid modified alkyd resin; 0.1 to 1 part of an initiator; 0.5 to 1 part of a curing accelerator; 0.1-1 part of a dispersant; 50 to 100 parts of filler; and 50-100 parts of a solvent. The copper-clad plate prepared from the resin glue solution can be quickly self-crosslinked at a relatively low temperature; hot pressing temperature is low, time is short, efficiency is high, cost is low, and energy is greatly saved; the product is not easy to warp, less in gummosis, more uniform in thickness, halogen-free in the whole process and environment-friendly; the copper-clad plate prepared by the invention can be comparable with a common FR-4 copper-clad plate in index, and is relatively high in stripping resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper clad laminate production, and in particular relates to a pressure-sensitive halogen-free high-stripping resistance resin adhesive and a copper clad laminate and a preparation method thereof. Background Art

[0002] As one of the countries with the greatest development potential in electronics in the world, my country has developed rapidly in the fields of electrical appliances, automobiles, railways, and aviation. The production of traditional copper clad laminates requires high temperature, high pressure, and long-term pressing. For example, the maximum pressing temperature of ordinary FR-4 copper clad laminates is 190-220°C, the pressing time is 150min-200min, and the maximum pressure is 2.5-3.5MPa, which wastes energy and is not conducive to energy-saving and efficient production. In terms of product performance, the greater the hot pressing pressure of the copper clad laminate, the greater the internal stress of the product, resulting in greater product warpage, which affects the processing of the printed circuit board and causes excessive glue flow, affecting many product properties. Summary of the invention

[0003] In view of the deficiencies of the above-mentioned prior art, the present invention provides a pressure-sensitive halogen-free high-stripping resistance resin glue and a copper-clad laminate and a preparation method thereof. The specific technical scheme is as follows:

[0004] The first object of the present invention is to provide a pressure-sensitive halogen-free high-stripping resistance resin adhesive, comprising the following components in parts by weight:

[0005] 5-15 parts of phenyl silicone resin; 10-25 parts of acrylic resin; 5-20 parts of modified epoxy resin; 10-20 parts of diene copolymer; 18-25 parts of acrylic modified alkyd resin; 0.1-1 part of initiator; 0.5-1 part of curing accelerator; 0.1-1 part of dispersant; 50-100 parts of filler; 50-100 parts of solvent.

[0006] The phenyl silicone resin of the resin glue of the present invention is a polysiloxane resin containing a benzene ring in the main chain. The molecular structure of the phenyl silicone resin is trapezoidal, which can make the polymer rigid and have a higher Tg; the organosilicon resin phenyl silicone resin and the acrylic resin are pressure-sensitive resins. As the main resins, the two can be cross-linked under high pressure without high temperature and have high adhesion performance; the modified epoxy resin increases the flexibility of the system. When the resin glue of the present invention is used to prepare copper clad laminates, it can be self-cross-linked quickly at a relatively low temperature, and does not need high-temperature pressing like traditional copper clad laminates, which greatly saves energy, and the product is not easy to warp, and has less glue flow. The copper clad laminates prepared can be comparable to the indicators of ordinary FR-4 copper clad laminates, and have higher peeling resistance.

[0007] Furthermore, the acrylic resin is a mixture of acrylate and methacrylate.

[0008] Furthermore, the molar ratio of the acrylic acid ester to the methacrylic acid ester is (1-3):1.

[0009] Furthermore, the modified epoxy resin is one or more of isocyanate-modified epoxy resin, dicyclopentadiene-modified epoxy resin or phosphorus-containing epoxy resin.

[0010] Preferably, the modified epoxy resin is an isocyanate modified epoxy resin, which can improve the heat resistance and adhesion of the copper clad laminate, and the manufactured product has high peeling resistance.

[0011] Preferably, the isocyanate-modified epoxy resin is a diphenylmethane diisocyanate-modified epoxy resin, and the structural formula is as follows:

[0012]

[0013] The diphenylmethane diisocyanate modified epoxy resin has strong adhesive force and toughness.

[0014] Furthermore, the epoxy equivalent of the diphenylmethane diisocyanate-modified epoxy resin is 280 to 330, and contains boric acid.

[0015] Furthermore, the diene copolymer is a polycycloolefin, such as polydicyclopentadiene, or a conjugated diene, such as 1,3-butadiene.

[0016] Furthermore, the acrylic acid modified alkyd resin is a copolymer prepared by esterification of acrylic acid and alkyd resin monomers in a molar ratio of (1-3):1.

[0017] Furthermore, the initiator is one or more of diisopropylbenzene peroxide, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, di-tert-butyl peroxide or azobisisobutyronitrile.

[0018] Preferably, the initiators are dicumyl peroxide and tert-butyl hydroperoxide.

[0019] Furthermore, the curing accelerator is 2-ethyl-4-methylimidazole, 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole or 2-undecylimidazole.

[0020] Preferably, the curing accelerator is 2-ethyl-4-methylimidazole, 2-phenylimidazole or 2-undecylimidazole.

[0021] Furthermore, the dispersant is one or more of epoxysilane dispersant, BYK W9010, and BYK W903, and BYK comes from BYK of Germany.

[0022] Furthermore, the epoxysilane dispersant is KH-560, A-187 or Z-6040.

[0023] γ-(2,3-epoxypropoxy) can significantly improve the mechanical and electrical properties of epoxy glass fiber cloth copper clad laminates cured by amide or anhydride.

[0024] Preferably, the dispersants are KH-560 and BYK W903, which are used simultaneously to increase the wettability of the adhesive to the glass fiber cloth, thereby making the glass fiber cloth and the adhesive better bonded.

[0025] Furthermore, the solvent is two or more of toluene, xylene, ethyl acetate and butyl acetate.

[0026] Preferably, the solvent is toluene, xylene, ethyl acetate, and butyl acetate. The combination of high and low boiling points can prevent defects such as craters and vertical strands from occurring during the gluing process, and can also allow the components to be fully dispersed.

[0027] Furthermore, the filling material is two or more of silicon dioxide, spherical silicon, soft silicon, talcum powder, E glass powder, alumina, and boehmite produced by a fusion process.

[0028] The silicon dioxide prepared by the melting method is prepared by melting crystalline silicon dioxide at high temperature and mechanically crushing it after cooling, and has lower dielectric properties and thermal expansion coefficient; spherical silicon has higher bulk density, and the prepared plate has uniform stress, good fluidity, good mechanical properties and good adhesion; soft silicon and talcum powder have low hardness, and the hardness of the filler is balanced.

[0029] Preferably, the filling material is a mixture of silica produced by a fusion process, E glass powder and alumina, wherein the silica produced by a fusion process is from SIBELCO Co., Ltd. of South Korea, and the alumina is aluminum oxyhydroxide.

[0030] The second object of the present invention is to provide a copper clad laminate, which is prepared from the above-mentioned pressure-sensitive halogen-free and highly peel-resistant resin adhesive.

[0031] The third object of the present invention is to provide a method for preparing the copper clad laminate, comprising the following steps:

[0032] (1) mixing components of a pressure-sensitive halogen-free and highly peel-resistant resin adhesive, emulsifying and stirring to obtain a resin adhesive;

[0033] (2) impregnating the electronic grade glass fiber cloth with the resin glue solution obtained in step (1), and passing through a glue coating machine at 100 to 150° C. to obtain a prepreg;

[0034] (3) stacking a plurality of prepregs obtained in step (2) together, and covering both sides with a copper foil to obtain a plate;

[0035] (4) The plate and the stainless steel plate are stacked up and down, and sent into a vacuum press at 70-160°C and 10-15kgf / cm2 The pressure-sensitive halogen-free copper clad laminate with high peel resistance is obtained by hot pressing for 40 to 60 minutes under the above conditions.

[0036] Furthermore, in the step (1), the phenyl silicone resin is first dissolved in a solvent. The phenyl silicone resin has poor solubility, and the solvent is used to dissolve it to improve the dissolution efficiency.

[0037] Furthermore, in the step (2), the electronic grade glass fiber cloth is treated with a silane dispersant.

[0038] Furthermore, in step (2), the electronic grade glass fiber cloth is any one of E glass fiber cloth and NE glass fiber cloth.

[0039] Furthermore, in the step (2), the gelling time of the prepreg is 100 to 150 seconds, and the gelling temperature is 150 to 170°C.

[0040] Furthermore, in the step (4), after the plate and the stainless steel plate are stacked up and down, high heat-resistant felt is laid first, and then the plate is sent into a vacuum press for hot pressing for 40 to 60 minutes.

[0041] The beneficial effects of the present invention are:

[0042] The resin glue of the present invention uses pressure-sensitive resin silicone resin and acrylic resin as the main resin. The copper-clad laminate prepared by using the resin glue of the present invention is pressure-sensitive and can be quickly self-crosslinked at a relatively low temperature. The hot pressing temperature is low, the time is short, the efficiency is high, the cost is low, and energy is greatly saved; because the hot pressing pressure is small, the product is not easy to warp, and the technical problems such as welded parts falling off in subsequent processing are solved; there is less glue flow and the thickness is more uniform, which is conducive to the subsequent processing of printed copper-clad laminates; and the whole process is halogen-free and environmentally friendly. The copper-clad laminate prepared by the present invention can be comparable to the indicators of ordinary FR-4 copper-clad laminates, and has higher peeling resistance. DETAILED DESCRIPTION

[0043] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0044] Embodiment 1:

[0045] A sensitive halogen-free high-stripping resistance copper-clad laminate, the preparation method of which comprises the following steps:

[0046] (1) By weight, 10 parts of methylphenyl polysiloxane and 20 parts of butyl acetate solution were pre-dissolved, and then mixed with 10 parts of acrylic resin (a mixture of acrylic acid ester and methacrylic acid ester in a molar ratio of 1:2), 10 parts of diphenylmethane diisocyanate modified epoxy resin (Tongyu New Materials (Guangdong) Co., Ltd., TER296k75), 10 parts of 1,3-butadiene; 25 parts of acrylic acid modified alkyd resin (Shandong Kafule Polymer Materials Co., Ltd., CFU1160), 0.1 parts of initiator diisopropylbenzene peroxide, 0.5 parts of curing accelerator 2-ethyl-4-methylimidazole, 0.1 parts of dispersant KH-560, 0.1 parts of BYK W903, 50 parts of silica prepared by a filler melting method (Sibelco Co., Ltd., Korea, 525); 50 parts of aluminum hydroxide, 25 parts of toluene, and 5 parts of butyl acetate, and emulsified and stirred for 1.5 hours to obtain a resin glue solution;

[0047] (2) impregnating electronic grade 2116 glass fiber cloth treated with dispersant KH-560 into the resin glue solution prepared in step (1), passing through a glue coating machine at 150° C. to obtain a prepreg, controlling the glue content to be 45% to 55%, and gelling at 160° C. for 100 to 150 seconds;

[0048] (3) stacking six prepregs obtained in step (2) together, and covering each side with a 35 μm copper foil to obtain a plate;

[0049] (4) The plate and the stainless steel plate are stacked up and down, and sent into the vacuum press. After preheating to 70°C, the heating rate is 3°C / min, and the pressure is increased to 15kgf / cm when it reaches 150°C. 2 The pressure-sensitive halogen-free copper clad laminate was obtained by hot pressing for 60 minutes under the above conditions.

[0050] Embodiment 2:

[0051] A sensitive halogen-free high-stripping resistance copper-clad laminate, the preparation method of which comprises the following steps:

[0052] (1) By weight, 10 parts of methylphenyl polysiloxane, 10 parts of acrylic resin (a mixture of acrylic acid ester and methacrylic acid ester in a molar ratio of 1:1), 10 parts of isocyanate-modified epoxy resin (TER296k75 of Tongyu New Materials (Guangdong) Co., Ltd.), 10 parts of dicyclopentadiene; 25 parts of acrylic acid-modified alkyd resin (CFU1160 of Shandong Kafule Polymer Materials Co., Ltd.), 0.1 parts of initiator tert-butyl hydroperoxide, 0.8 parts of curing accelerator 2-phenylimidazole, 0.1 parts of dispersant KH-560, 0.1 parts of BYK W903, 40 parts of silica prepared by a filler melting method (525 of Sibelco Co., Ltd., Korea); 50 parts of aluminum hydroxide, 30 parts of xylene, and 20 parts of butyl acetate were mixed and emulsified and stirred for 2 hours to obtain a resin glue solution;

[0053] (2) impregnating electronic grade 2116 glass fiber cloth treated with dispersant KH-560 into the resin glue solution prepared in step (1), passing through a glue coating machine at 150° C. to obtain a prepreg, controlling the glue content to be 45% to 55%, and gelling at 160° C. for 100 to 150 seconds;

[0054] (3) stacking six prepregs obtained in step (2) together, and covering each side with a 35 μm copper foil to obtain a plate;

[0055] (4) The plate and the stainless steel plate are stacked up and down, and sent into the vacuum press. After preheating to 70°C, the heating rate is 3°C / min, and the pressure is increased to 15kgf / cm when it reaches 150°C. 2 The pressure-sensitive halogen-free copper clad laminate was obtained by hot pressing for 50 minutes under the above conditions.

[0056] Comparative Example 1:

[0057] A halogen-free FR-4 copper clad laminate, the preparation method of which comprises the following steps:

[0058] (1) By weight, 2 parts of tetraphenol ethane epoxy, 30 parts of bis-DOPO modified epoxy resin, 20 parts of bisphenol A epoxy resin, 1 part of cross-linking curing agent dicyandiamide, 30 parts of linear phenolic acid, 0.01 parts of accelerator 2-methylimidazole, 0.5 parts of dispersant BYK-W903, 10 parts of solvent propylene glycol monomethyl ether, 10 parts of ethylene glycol methyl ether, 10 parts of aluminum hydroxide, and 20 parts of silicon powder were mixed, emulsified and stirred to obtain a resin glue;

[0059] (2) dipping the 2116 electronic grade glass fiber cloth treated with dispersant KH-560 into the resin glue solution prepared in step (1), passing through a glue coating machine at 170° C., controlling the glue content to be 45% to 55%, and controlling the gelling time to be 95 seconds, to obtain a prepreg;

[0060] (3) 6 prepregs prepared in step (2) are stacked together and coated with a 35 μm copper foil on both sides to obtain a plate;

[0061] (4) The plate is stacked with the stainless steel plate, covered with high heat-resistant felt, and sent into the vacuum press. After preheating to 60°C, the initial pressure is 10kgf / cm 2 , control the heating rate to 3℃ / min, when the outer layer material temperature reaches 100℃, increase the temperature and pressure to 220℃, 30kgf / cm 2 The halogen-free FR-4 copper clad laminate was obtained by hot pressing for 120 min under the above conditions.

[0062] Comparative Example 2:

[0063] A halogen-free copper clad laminate, the preparation method of which comprises the following steps:

[0064] (1) By weight, 10 parts of methylphenyl polysiloxane; 10 parts of acrylic resin (a mixture of acrylic acid ester and methacrylic acid ester in a molar ratio of 1:1); 10 parts of ordinary epoxy resin E51; 10 parts of dicyclopentadiene; 25 parts of acrylic acid modified alkyd resin (Shandong Kafule Polymer Materials Co., Ltd., CFU1160), 0.1 parts of initiator tert-butyl hydroperoxide; 0.8 parts of curing accelerator 2-phenylimidazole; 0.1 parts of dispersant KH-560, 0.1 parts of BYK W903, 40 parts of silica prepared by a filler melting method (Sibelco Co., Ltd., Korea, 525), 50 parts of aluminum oxide hydroxide, 30 parts of xylene, and 20 parts of ethyl acetate were mixed, emulsified and stirred to obtain a resin glue solution;

[0065] (2) impregnating the electronic grade 2116 glass fiber cloth treated with dispersant KH-560 with the resin obtained in step (1), and passing through a 150° C. glue coating machine to obtain a prepreg, wherein the glue content is controlled to be 45% to 55%, and the gelling time at 160° C. is 100 to 150 seconds;

[0066] (3) stacking six prepregs obtained in step (2) together, and covering each side with a 35 μm copper foil to obtain a plate;

[0067] (4) The plate and the stainless steel plate are stacked up and down, and sent into the vacuum press. After preheating to 70°C, the heating rate is 3°C / min, and the pressure is increased to 15kgf / cm when it reaches 150°C. 2 The pressure-sensitive halogen-free copper clad laminate was obtained by hot pressing for 50 minutes under the above conditions.

[0068] The performance test data of the copper clad laminate samples obtained in the embodiments and comparative examples are shown in Table 1.

[0069] Table 1 Comparison table of various performance test data of samples obtained from the embodiments and comparative examples

[0070]

[0071] Tg (℃): Differential scanning calorimetry (DSC), IPC TM-650;

[0072] T288 (min): Thermomechanical analysis (TMA), IPC TM-650;

[0073] Flame retardant, anti-peeling and warping are all methods in IPC TM-650.

[0074] It can be seen from Table 1 that the copper clad laminate prepared in the embodiment requires lower pressing temperature, pressing pressure and pressing time. Compared with the comparative example, the copper clad laminate prepared in the embodiment has excellent peeling resistance, less warping, and flame retardancy and Tg comparable to the commonly used halogen-free FR-4 board, which can meet the fields of household appliances, lamps and lanterns, greatly improves production efficiency, saves energy consumption, and has low cost. In addition, during the preparation process of the copper clad laminate in the embodiment, there is less glue flow, and the thickness of the obtained copper clad laminate is more uniform, which is beneficial to the subsequent processing of the printed copper clad laminate.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A pressure-sensitive halogen-free, highly peel-resistant resin adhesive, characterized in that: The composition comprises the following components in parts by weight: 5-15 parts of phenyl silicone resin; 10-25 parts of acrylic resin; 5-20 parts of modified epoxy resin; 10-20 parts of diene copolymer; 18-25 parts of acrylic modified alkyd resin; 0.1-1 part of initiator; 0.5-1 part of curing accelerator; 0.1-1 part of dispersant; 50-100 parts of filler; 50-100 parts of solvent.

2. The pressure-sensitive halogen-free and highly peel-resistant resin adhesive according to claim 1, characterized in that: The acrylic resin is a mixture of acrylate and methacrylate.

3. The pressure-sensitive halogen-free and highly peel-resistant resin adhesive according to claim 1, characterized in that: The modified epoxy resin is one or more of isocyanate modified epoxy resin, dicyclopentadiene modified epoxy resin or phosphorus-containing epoxy resin.

4. The pressure-sensitive halogen-free and highly peel-resistant resin adhesive according to claim 1, characterized in that: The diene copolymer is a polycycloolefin or a conjugated diene.

5. The pressure-sensitive halogen-free and highly peel-resistant resin adhesive according to claim 1, characterized in that: The acrylic acid modified alkyd resin is a copolymer prepared by esterification of acrylic acid and alkyd resin monomers in a molar ratio of (1-3):

1.

6. The pressure-sensitive halogen-free and highly peel-resistant resin adhesive according to claim 1, characterized in that: The initiator is one or more of diisopropylbenzene peroxide, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, di-tert-butyl peroxide or azobisisobutyronitrile; the curing accelerator is 2-ethyl-4-methylimidazole, 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole or 2-undecylimidazole; the solvent is two or more of toluene, xylene, ethyl acetate and butyl acetate.

7. The pressure-sensitive halogen-free and highly peel-resistant resin adhesive according to claim 1, characterized in that: The dispersant is one or more of epoxysilane dispersant, BYK W9010, and BYK W903.

8. The pressure-sensitive halogen-free and highly peel-resistant resin adhesive according to claim 1, characterized in that: The filling material is two or more of silicon dioxide, spherical silicon, soft silicon, talcum powder, E glass powder, aluminum oxide and boehmite obtained by a melting process.

9. A copper clad laminate, characterized in that: The adhesive is prepared from the pressure-sensitive halogen-free and highly peel-resistant resin solution described in any one of claims 1 to 8.

10. A method for preparing a copper clad laminate, characterized in that: The steps include: (1) mixing the pressure-sensitive halogen-free and highly peel-resistant resin adhesive liquid components described in any one of claims 1 to 8, emulsifying and stirring to obtain a resin adhesive liquid; (2) impregnating the electronic grade glass fiber cloth with the resin glue solution obtained in step (1), and passing it through a glue coating machine at 100 to 140° C. to obtain a prepreg; (3) stacking a plurality of prepregs obtained in step (2) together, and covering both sides with a copper foil to obtain a plate; (4) The plate and the stainless steel plate are stacked up and down, and sent into a vacuum press at 70-160°C and 10-15kgf / cm 2 The pressure-sensitive halogen-free copper clad laminate with high peel resistance is obtained by hot pressing for 40 to 60 minutes under the above conditions.

Citation Information

Patent Citations

  • Glue solution for halogen-free high-CTI copper-clad plate as well as preparation method and application thereof

    CN111704785A

  • High-strength acrylate modified organic silicon pressure-sensitive adhesive and preparation method thereof

    CN116042104A

  • Cold-resistant and heat-resistant acrylic pressure-sensitive adhesive as well as preparation method and application thereof

    CN117106390A

  • Preparation method of halogen-free and phosphorus-free copper-clad plate

    CN117584597A